2019
DOI: 10.5223/pghn.2019.22.6.619
|View full text |Cite
|
Sign up to set email alerts
|

Down the Rabbit Hole-Considerations for Ingested Foreign Bodies

Abstract: We report the case of a seven-year-old boy with an ingested foreign body, which was retained within the appendix for a known duration of ten months, ultimately requiring appendectomy. The ingested foreign body was incidentally discovered by abdominal x-ray at an emergency room visit for constipation. Despite four bowel cleanouts, subsequent x-rays showed persistence of the foreign body in the right lower quadrant. While the patient did not have signs or symptoms of acute appendicitis, laparoscopic appendectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Likewise, asymptomatic patients may even have forgotten the ingestion by not giving importance to it, missing an important pillar in the presumptive etiological diagnosis [4,11,12]. It has been reported that up to 29% of retained appendiceal foreign bodies are asymptomatic [11]. In the clinical case presented here, poorly controlled psychiatric pathology was denoted as a risk factor.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Likewise, asymptomatic patients may even have forgotten the ingestion by not giving importance to it, missing an important pillar in the presumptive etiological diagnosis [4,11,12]. It has been reported that up to 29% of retained appendiceal foreign bodies are asymptomatic [11]. In the clinical case presented here, poorly controlled psychiatric pathology was denoted as a risk factor.…”
Section: Discussionmentioning
confidence: 76%
“…Appendiceal symptoms are a red focus in the clinical evaluation after the ingestion of objects; however, linking foreign body ingestion with appendiceal symptoms is usually difficult, especially in psychiatric patients with poor self-care or lack of control of their underlying pathology. Likewise, asymptomatic patients may even have forgotten the ingestion by not giving importance to it, missing an important pillar in the presumptive etiological diagnosis [4,11,12]. It has been reported that up to 29% of retained appendiceal foreign bodies are asymptomatic [11].…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates tend to be higher in asymptomatic patients with a delayed diagnosis over 48 hours. Children with a history of dysphagia and drooling are prone to high suspicion of FB ingestion, and radiographic evaluation should be conducted [ 2 , 4 , 5 ]. Radiopaque inorganic objects are better identified on x-rays.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report of magnets being impacted in the appendix. Other foreign bodies encountered in the pediatric population and found in PubMed and Google Scholars were metallic screws, needles, firearm pellets, hazelnut, canine hair, sand and stones, metal coil, seeds, the tip of mercury thermometer, plastic pieces, metal beads, nail, and a small blunt metallic object [7][8][9][10][11][12][13][14][15][16][17][18][19]. Upon reviewing the previous case reports, 21 cases were found.…”
Section: Discussionmentioning
confidence: 99%